Percep????o dos res??duos s??lidos pela popula????o como instrumento para o seu gerenciamento na cidade de Bertioga - SP - Araujo, Nat??lia Aparecida Braconaro de (2016)
In addition to generating public health problems, the disposal of municipal solid waste [MSW] in coastal areas modifies the environment and can change the way people perceive it. Problems such as a lack of proper management of landfills, centralization of waste management actions, absence or low cost of taxes for waste collection and disposal, as well as low participation of population in waste reduction and recycling actions that make it unfeasible to maintain a waste management system. These issues, as well as a lack of technologies for waste separation and disposal, lead to a need for strategies that will help a city council in the choice and implementation of measures that are economically viable, have the capacity to self-sustain and involve all social spheres in its application. The objective of this research is to make a diagnosis about the MSW???s perception by residents of the city of Bertioga-SP, in order to assist in the city MSW management, in a way that increases the indexes of municipality recycling. Five groups of hypotheses about which factors influence the perception and social participation in MSW management were created. The data to test the hypotheses were obtained through a questionnaire created by the author of the research and applied to residents of Bertioga. These data were analyzed statistically, being the dissertative data analyzed by semantic analysis software. The results showed that access to the internet has direct influence at the acces to the information about the correct waste disposal (p=0,000), as was noted that citizens with more contact with neighbors or relatives tend to adopt better waste disposal practices (p=0,464). In the semantic analysis it was evident that the lack of communication between public cleaning companies and citizens, as well as failures in the logistics of waste collection had a negative influence on their participation in waste disposal actions.Despite this, positive actions were found in waste management, such as the use of cooking oil for the production of soap for residents. With analysis of the hypotheses, waste management strategies were elaborated, wich will be implemented by the RSU Energia Project, whose this research its part, to improve the MSW management and, later, for the improvement of the waste management of the entire Baixada Santista region.